2016
DOI: 10.1002/hep.28923
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in liver transplant wait‐listing in the era of direct‐acting antiviral therapy

Abstract: Recent approval of direct-acting antiviral (DAA) therapy for patients with decompensated cirrhosis (DC) secondary to hepatitis C (HCV) is associated with improved hepatic function. We analyzed trends in liver transplant (LT) wait-listing (WL) to explore potential impact of effective medical therapy on WL registration. This is a cohort study using the Scientific Registry of Transplant Recipients database from 2003-2015. 47,591 adults wait-listed for LT from HCV, hepatitis B (HBV) and non-alcoholic steatohepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
157
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(168 citation statements)
references
References 36 publications
(69 reference statements)
8
157
0
3
Order By: Relevance
“…The decrease in HCV‐related listings is likely a reflection of the effectiveness of the latest generation of DAAs and has been shown in other population studies. Flemming et al reported a 30% decrease in the rate of HCV‐related listings with the advent of the latest DAAs, and a 34% rate increase in HCV‐HCC listings. While Van der Meer et al showed that patients who achieved SVR with interferon had a significantly lower cumulative HCC occurrence (5.1%; 95% CI: 1.3%‐8.9%) compared to patients who did not achieve SVR (29.9%; 95%CI: 24.3%‐35.5%), the improvements in hepatic dysfunction and fibrosis progression may outpace the decreased risk of HCC associated with SVR .…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in HCV‐related listings is likely a reflection of the effectiveness of the latest generation of DAAs and has been shown in other population studies. Flemming et al reported a 30% decrease in the rate of HCV‐related listings with the advent of the latest DAAs, and a 34% rate increase in HCV‐HCC listings. While Van der Meer et al showed that patients who achieved SVR with interferon had a significantly lower cumulative HCC occurrence (5.1%; 95% CI: 1.3%‐8.9%) compared to patients who did not achieve SVR (29.9%; 95%CI: 24.3%‐35.5%), the improvements in hepatic dysfunction and fibrosis progression may outpace the decreased risk of HCC associated with SVR .…”
Section: Discussionmentioning
confidence: 99%
“…Annual standardized incidence rates of wait‐listing were compared depending on the indication for transplantation (HCV, HBV or NASH). While the number of patients on the waiting list for NASH increased and the number listed for HBV remained fairly stable, the number of patients listed for decompensated cirrhosis secondary to HCV fell by 32% in the era of DAA therapy as compared to the IFN era and is now equal to that of NASH …”
Section: Hepatic Benefits Of Hcv Cure and Remaining Challengesmentioning
confidence: 99%
“…1 Furthermore, data through 2015 demonstrated a decline in the number of HCV-related LT waitlist registrations and LT surgeries following the introduction of DAA-based regimens. 2,3 Despite the downtrend, primary diagnosis of HCV remained the most common cause for liver transplantation in the United States until the end of 2015. 3 In this updated report, we evaluated the current impact of DAA era on the rate of HCV-related liver transplantation in the United States.…”
mentioning
confidence: 99%
“…2,3 Despite the downtrend, primary diagnosis of HCV remained the most common cause for liver transplantation in the United States until the end of 2015. 3 In this updated report, we evaluated the current impact of DAA era on the rate of HCV-related liver transplantation in the United States.…”
mentioning
confidence: 99%